"Könsrollen som kvinna bet inte heller på mitt beroende" - En kvalitativ studie om hur kvinnliga alkoholmissbrukare skildrar sina erfarenheter i självbiografier - Drakenberg Dahlgren,Ellen; Sandström,Anna (2023)
The aim of this study was to examine how women who have been in an alcohol addiction describe their experiences of being a woman who has an alcohol addiction and the possible shame and stigma related to it. We used Goffman's theory about stigma, narrative theory, and Judith Butler's theory of gender. The study was to be carried out based on their narrative in the form of autobiographies. Our selection criteria were women with alcohol addiction, the author had to be the person who had experienced it and the autobiographies had to take place in a Swedish context. The books also had to be available in Lund´s libraries. In this study, a qualitative research method was used in the form of narrative analysis. The most important results were that the authors had experienced shame and stigma linked to their addiction. This affected them in different ways, mostly negatively. Their experiences of being a woman with alcohol addiction were related to norms and ideals. It was clear to us that the women in the autobiographies have a hard time living up to the expectations that come with being a woman because of their alcohol addiction.
Keywords: Autobiography; alcohol addiction; narrative analysis; stigma; female ideal